Prying Eyes in the Sky: Visual Aerial Surveillance of Private Residences as a Tort - Friedman, Jeremy (Science and Technology Law Review, 2002)
Landowners owned all airspace directly above their property, prior to U.S. v. Causby, a 1946 Supreme Court ruling that made the sky a “public highway” without clearly specifying whether landowners retained any rights to restrict overhead non-transportation activities. In recent decades, technological advances have made possible aircraft and satellite surveillance that enables visual surveillance of private property. Technological advances also allow the data recorded by such surveillance to be stored and potentially sold in a market for information. As a result, landowners are left vulnerable to troubling surveillance that creates asymmetries of information, usurps the value of property, and constitutes an invasion of privacy. The privacy tort of intrusion would offer a common law remedy for landowners, if the law were applied properly, in a manner distinguishing aerial surveillance from ground-level surveillance. However, due to imperfections in intrusion doctrine, the optimal solution would be to enact legislation codifying the conclusion that visual aerial surveillance of private property subjects the observer to tort liability. Liability could be avoided where the observer points to strong countervailing considerations, such as a compelling reason for undertaking the surveillance and the demonstration of prudence in recording and storing data. Creating a presumption of tort liability would not create insurmountable practical problems and would provide analogous protection to that offered under existing wiretapping law.